Improving the Informed Consent Process for Research Subjects with Low Literacy: A Systematic Review - Tamariz, Leonardo; Palacio, Ana; Robert, Mauricio; Marcus, Erin N. (Journal of general internal medicine : JGIM, 2013)
ABSTRACT BACKGROUND Inadequate health literacy may impair research subjects’ ability to participate adequately in the informed consent (IC) process. Our aim is to evaluate the evidence supporting interventions, to improve comprehension of the IC process in low literacy subjects. METHODS We performed a MEDLINE database search (1966 to November 2011) supplemented by manual searches of bibliographies of key relevant articles. We selected all studies in which a modification of the IC was tested to improve comprehension in low literacy populations. Study design, quality criteria, population, interventions and outcomes for each trial were extracted. The main outcome evaluated was comprehension, measured using a written test or verbal comprehension. RESULTS Our search strategy yielded 281 studies, of which only six met our eligibility criteria. The six studies included 1620 research participants. The studies predominantly included populations that were older (median age 61, range 48–64), ethnic minority, and with literacy level of 8th grade or below. Only one study had a randomized design. The specific intervention differed in each study. Two of the studies included the teach-back method or teach to goal method and achieved the highest level of comprehension. Two studies changed the readability level of the IC and resulted in the lowest comprehension among study subjects. CONCLUSIONS The evidence supporting interventions to improve the informed consent process in low literacy populations is extremely limited. Among the interventions evaluated, having a study team member spend more time talking one-on-one to study participants was the most effective strategy for improving informed consent understanding; however, this finding is based on the results of a single study.